DIMENSI HUKUM PEMBEBASAN LAHAN: HAK, PERATURAN, DAN REFORMASI - Noor, Aslan; Hermindo, Hermindo; Setiawati, Yeti; Wijaya, Melliana; Rohmani, Rodiah (Legal Standing : Jurnal Ilmu Hukum, 2024)
Policies and legal norms regarding land acquisition in Indonesia are generally regulated in Law (UU) no. 2 of 2012 concerning Land Acquisition for Development in the Public Interest. Development policies and projects, such as infrastructure, industrial zones, or public facilities, often require significant space that can only be obtained through land acquisition. This research aims to comprehensively review the legal dimensions related to land acquisition, focusing on the rights concerned, applicable regulations, and the need for reform to ensure a fair and sustainable process. This research uses normative juridical research methods, with comparative, conceptual and statutory approaches. These data were analyzed descriptively and qualitatively. The results of this research show that land acquisition in Indonesia is regulated by various laws, including the Job Creation Omnibus Law and Government Regulation no. 19/2021. The land acquisition process involves stages of planning, preparation, implementation and delivery of results, involving many government agencies. Policy and regulatory reform in land acquisition is essential to address gaps and deficiencies in the existing system, with particular emphasis on protecting community rights, promoting transparency, and ensuring accountability. Increasing equity in land acquisition involves strategies to ensure impartiality, transparency and protection of the interests of all stakeholders.